Analisis Pengaruh Kualitas Layanan Informasi Swamedikasi Online Berbasis Whatsapp Bot Terhadap Kepuasan Masyarakat - Widyaningrum, Esti Ambar; Yestari, Farah Eka Julia; Sari, Erni Anika; Srihartini, Indah (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
Abstract: The innovation of online self-medication information services, one of which is based on WhatsApp Bot, is needed to make it easier for people to find self-medication information for the community. This innovation needs to be continuously developed so that it can provide adequate information services, can increase knowledge and provide satisfaction to users. The purpose of this study was to determine the level of community satisfaction with online self-medication services based on WhatsApp Bot and the effect of expectations on satisfaction using the RATER dimension (Reliability, Assurance, Tangible, Empathy, Responsiveness) in the community of Talun Village, Blitar Regency. The method used in this study is an analytical survey using a cross sectional design. Sampling was done by purposive sampling technique and obtained 264 respondents from the residents of Talun Village, Blitar Regency. Gap analysis was obtained at -0.10 with a level of satisfaction that was not satisfied with the services that had been provided with detailed attributes including: layout, absence of constraints, valid and reliable information, complete information, attention to user needs and the speed of customer service responding, needs to be improved to increase user satisfaction. Spearman rank correlation test obtained P value 0.05 and correlation coefficient value of 0.644. The community is not satisfied with this information service and there is an influence between the quality of information source services and satisfaction in the community of Talun Village, Blitar Regency with a positive correlation and strong correlation strength so it is necessary to develop this Whatsapp Bot-based self- medication information service.